2023
DOI: 10.1007/s11756-023-01502-7
|View full text |Cite|
|
Sign up to set email alerts
|

Structure of forest stands of alien tree Quercus rubra in Central Europe

Jana Májeková,
Jana Medvecká,
Katarína Mikulová
et al.

Abstract: The diversity of planted forest stands of the alien species Quercus rubra L. in Central Europe was studied. The northern red oak is a neophyte that has been cultivated in Europe since the seventeenth century as an ornamental as well as a useful tree. In 38 phytosociological relevés from Slovakia, Poland and the Czech Republic, we recorded a total of 223 vascular plant taxa, of which 10% were alien (with 9 invasive species). The stands were species-poor compared to the most native forests, with an average of 17… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 30 publications
0
2
0
2
Order By: Relevance
“…Nevertheless, woody plants are not usually regarded as significant invasive alien species (Richardson and Rejmánek 2011;Hegedüšová Vantarová et al 2023). However, Májeková et al (2023) confirmed that planted alien Quercus rubra forest stands in Central Europe influence the diversity and cover of the herb layer. Moreover, the dense canopy of Q. rubra and the large cover of litter consisting mainly of fallen old red oak leaves affected the species richness of the undergrowth.…”
Section: Contributions Of the Special Issuementioning
confidence: 93%
See 1 more Smart Citation
“…Nevertheless, woody plants are not usually regarded as significant invasive alien species (Richardson and Rejmánek 2011;Hegedüšová Vantarová et al 2023). However, Májeková et al (2023) confirmed that planted alien Quercus rubra forest stands in Central Europe influence the diversity and cover of the herb layer. Moreover, the dense canopy of Q. rubra and the large cover of litter consisting mainly of fallen old red oak leaves affected the species richness of the undergrowth.…”
Section: Contributions Of the Special Issuementioning
confidence: 93%
“…habitat fragmentation . Moreover, the abandonment of traditional management also leads to grassland encroachment by trees and shrubs (Palaj and Kollár 2021;Sanjuán et al 2018;Valkó et al 2018) as well as the spread of non-native and invasive species (Hejda et al 2009;Crawford and Rudgers 2012;Delimat and Kiełtyk 2019;Axmanová et al 2021;Hejda et al 2021;Hegedüšová Vantarová et al 2023;Májeková et al 2023). Invasive species constitute one of the most significant threats to biodiversity and have an impact on many ecosystems worldwide (Keller et al 2011;Dawson and Schrama 2016;Pyšek et al 2020;Ikinci 2022;Kochjarová et al 2023;Shevera 2024).…”
Section: Introductionmentioning
confidence: 99%
“…Загальне видове багатство усіх досліджених типів лісів співмірне з аналогічними центральноєвропейськими показниками (Májeková et al, 2023), зокрема, нами зафіксовано 232 види судинних рослин, з яких 13 (або 6% від загальної кількості) є адвентивними, що, за виключенням двох, є інвазійними. Натомість у лісах Центральної Європи трапляються загалом 223 види, з яких 10% є адвентивними, а 9 видів -інвазійними (Májeková et al, 2023). Одним із очікуваних результатів наших досліджень стало найнижче видове багатство рослинних угруповань чистих насаджень Q. rubra.…”
Section: результатиunclassified
“…Схожі результати дослідження лісів з участю Q. rubra в Центральній Європі отримано словацькими вченими (Májeková et al, 2023). Узагальнюючи наявні європейські та українські дані щодо лісових рослинних угруповань за участю Q. rubra спостерігаємо тенденцію до збіднення їхнього флористичного різноманіття, зокрема загальна кількість видів у таких фітоценозах зменшується з 30-40 до 17, а проєктивне покриття інших видів не перевищує 5%.…”
Section: обговоренняunclassified